Multivariate calibration of Fourier transform infrared spectra in determining iodine value of palm oil products - Che Man, Y.B; Setiowaty, G (Elsevier, 1999)
The Fourier transform infrared (FT-IR) spectra of palm oil samples, in the range between 3025 and 2992 cm-1, were used to compare different multivariate calibration techniques for quantitative iodine value (IV) determination. Forty-two spectra of palm oil with IV ranging between 53 and 65 were used to create calibration models based on partial least squares (PLS) and principle component regression (PCR) methods using different baseline types. The methods were compared with respect to the number of factors, coefficient of determination (R2) and accuracy of estimation. The standard error of prediction (SEP) ratios were calculated to compare the prediction capabilities of these calibration methods. The calibration models generated the number of factors from 3 to 7, R2 of 0.94443 to 0.98853, standard error of estimation (SEE) of 0.32 to 0.69 and SEP ratios of 1.43 to 13.48.